Green Auto Mobile Vehicle Design - Khan, M. A.; Saiful Islam, A. T. M.; Mamun, A. A.; Karim, T. (International Journal of Electrical Engineering and Applied Sciences (IJEEAS), 2023)
The grid line power crisis is very common in a developing country like Bangladesh. Due to the development of roads and public demands, the number of electric transports are increasing. This has caused for the increase in power consumption for charging the battery of that vehicles. Therefore, to reduce the power consumption of the national gridline for charging electric vehicles, solar energy-based vehicle such as solar energy-based auto-rickshaw, auto-cars are desired. Furthermore, the global warming is increasing due to pollution, deforestation, over uses of fuel-based vehicles, running of industries and etc. Depletion of the ozone layer due to greenhouse gas releases from vehicles will be one of the world’s main problems in the future. So, it would be a solution to the above-mentioned issues if solar cars were introduced. This research project aims to develop, implement and deal with the aspects of the photovoltaic vehicle that play an essential role in ensuring a future without energy crisis.